Dompet Dhuafa Development Communication in the DD Clinic Program, South Tangerang as a Form of Realizing SDGs Efforts - Ahmad Rifqi Arief Maulana; Iza Ma’rifah; Edi Amin; Tantan Hermansah; Muhammad Fanshoby (al-Afkar, Journal For Islamic Studies, 2025)
Dompet Dhuafa is a philanthropic institution whose funding comes from zakat, infaq, and shodaqoh. The donations are made by donors voluntarily. Equitable distribution of health care in efforts to improve SDGs is urgently needed, especially for the poor and isolated areas. The DD Clinic Ciputat Program, South Tangerang is a comprehensive, multidisciplinary service with an approach to improving the quality of life of patients and families facing health problems. This paper states that. As an analysis, this paper uses As an analysis Dompet Dhuafa is a philanthropic institution whose funding comes from zakat, infaq, and shodaqoh as well as the distribution of sacrificial animals. Distribution to areas in need (poor, underdeveloped, remote, disaster-prone, and conflict-prone areas) is divided into three theoretical dichotomies. First, the theory on Development Communication explains that Communication is an important partner in initiatives involving voluntary behavior change. The Islamic concept offered is Amal pious (عمل صالح) which explains sincere actions in carrying out worship or fulfilling religious obligations. Second, the Millennium Development Goals (MDGs), which emphasize the goals and responsibilities of all countries participating in the Millennium Summit, the Islamic concept offered is Ash-shodaqoh (الصَّدَقٰتِ) which is from the word sidq (sidiq) which means "truth". Third, the strategic communication of “Seven Threads” discusses the important aspects of development initiatives in the fields of health, nutrition, agriculture, family planning, education and community economy, while the Islamic concept is Basyiir (بَشِيْر) which means Bringer of good news. The findings are that Dompet Dhuafa is one of the philanthropic institutions. Its funding uses zakat, Infaq, and shodaqoh as well as the distribution of sacrificial animals. Dompet Dhuafa has a DD Clinic Program in Ciputat, South Tangerang, improving health for mustahiq. Distribution to areas in need, isolated areas are underdeveloped areas, remote areas, disaster-prone and conflict-prone.